2021
DOI: 10.37275/oaijss.v4i2.44
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning with Science-Technology-Society Approachment: a Literature Review

Abstract: One of the efforts made so that humans are able and able to develop theirpotential is through a learning process. Blended learning encourage sstudents to be more active and increases independence in learning.Students are required to learn and access material independently, andcomplete assignments given by the teacher, both individually and in groups.This literature review aims to discuss strategies for implementing blende dlearning as a student learning method. With the development of science andtechnology whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…61.84%), perceived usefulness of Google Classroom (76.08%), the student's satisfaction with Google Classroom (74.28%), and perceived instruction delivery on Google Classroom (66.70%) indicators stayed in the good category. Even though all of the students had shown positive perceptions towards Google Classroom used as an online learning media during the pandemic, there were still a few students who gave neutral or negative perceptions of google classroom used as an online learning media in a few indicators as they believed that face-to-face learning was still being the primary and most common types of learning(Huda et al, 2021).Based on a psycholinguistic standpoint, research findings suggest that students' perception of online learning through Google Classroom has demonstrated beneficial effects. The study identified positive outcomes across six different parameters evaluated via tests and interviews within the realm of English language instruction.…”
mentioning
confidence: 99%
“…61.84%), perceived usefulness of Google Classroom (76.08%), the student's satisfaction with Google Classroom (74.28%), and perceived instruction delivery on Google Classroom (66.70%) indicators stayed in the good category. Even though all of the students had shown positive perceptions towards Google Classroom used as an online learning media during the pandemic, there were still a few students who gave neutral or negative perceptions of google classroom used as an online learning media in a few indicators as they believed that face-to-face learning was still being the primary and most common types of learning(Huda et al, 2021).Based on a psycholinguistic standpoint, research findings suggest that students' perception of online learning through Google Classroom has demonstrated beneficial effects. The study identified positive outcomes across six different parameters evaluated via tests and interviews within the realm of English language instruction.…”
mentioning
confidence: 99%